THE EFFECT OF PBL MODEL WITH GOOGLE SITE WEB-ASSISTED ON STUDENTS' CRITICAL THINKING SKILLS ON TEMPERATURE, HEAT AND EXPANSION SUBJECT - N.G, Cahyani; Evita Putri, Rahmah; Yurnetti; Diliarosta, Skunda (UNIVERSITAS NEGERI MEDAN, 2024)
The purpose of this research is to determine the influence of the Problem Based Learning model assisted by Google Site Web on students' critical thinking skills on temperature, heat and expansion materials. The type of research used is Quasi Experiment with a Non-equivalent Control Group Design. The sample was taken using the Purposive Sampling technique, so that 65 students of SMP N 2 Payakumbuh were selected for grades VII 9 and VII 10. Data collection is carried out by giving pretest and posttest questions. Based on the data obtained, the tests used are the t-test for pretest and posttest. The t-test in the pretest obtained a tcount value = 3.68 > a ttable of 2.00 which means that there is a significant difference so that Ha is accepted. Meanwhile, in the t-posttest test, the tcount value = 2.29 > ttable 2.00 which means that there is a significant difference in the average of the experimental and control classes. So, based on the results obtained from the mean difference test, it was found that there was a significant difference between the average of the experimental and control classes before and after being given treatment. When we get different research results, to see the effect can be seen from the improvement of the learning outcomes of the two sample classes. Therefore, the N-gain test is used. The results of the hypothesis calculation used are the U test or the Man Whitney test because the data obtained on the N-gain is abnormal but homogeneous. The result of the u test was obtained Zhitung = -1.54 < Ztabel = - 0.73. Referring to the criteria of the u test which states that if the Zhitung < Ztabel then H0 is rejected. So in conclusion, there is an effect of significantly improving student learning outcomes between control and experimental classes. Keywords: PBL, Google, Site, Critical, Thinking.